Límite Pirineos. Una mirada global a la participación de anarquistas españoles en la Resistencia francesa - Diego Gaspar Celaya (Cahiers de Civilisation Espagnole Contemporaine)
Between 1940 and 1945 more than 10,000 Spaniards, thousands of them anarchists, mostly refugees in French territory as a result of the Spanish Civil War, fought in the French Resistance ranks. Incorporated in their interior branch, they participated in the liberation of several departments of the southern France and in the interception of German troops. They also carried out numerous sabotages and released numerous political prisoners of several metropolitan prisons. As part of the armies of free France, the external Resistance, thay fought the Axis troops from Bir Hakeim to Berchtesgaden, passing through the Alamein, Tunisia, Normandy, Rome, Paris or Strasbourg. Overcoming the factors that have made the study of Spanish participation in the French Resistance random for a number of years, this article aims to provide a renovated overview of the Spanish anarchist participation in French Resistance through a detailed analysis of the different resistant commitments carried out by them during the second world conflict. But without giving up a critical look at the historical-cultural approaches and positive myths that have contaminated its history for years.